If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -4x = 27x Solving 15 + -4x = 27x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27x' to each side of the equation. 15 + -4x + -27x = 27x + -27x Combine like terms: -4x + -27x = -31x 15 + -31x = 27x + -27x Combine like terms: 27x + -27x = 0 15 + -31x = 0 Add '-15' to each side of the equation. 15 + -15 + -31x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -31x = 0 + -15 -31x = 0 + -15 Combine like terms: 0 + -15 = -15 -31x = -15 Divide each side by '-31'. x = 0.4838709677 Simplifying x = 0.4838709677
| y-(-3)=-(9/2)(x-1) | | 11-3x=14x | | (x+6-5y)=(x-4+8) | | -24=-4/3y | | -(x+6-5y)=(x-4+8) | | 2(2x+3)3(5x+4)= | | (0.25*X)+X=3665.00 | | 6-2z=18-3z | | -3/4w=15 | | f*4+5=11 | | .25x=1567.50 | | (a+3)(a+3)=0 | | 3cos^2(x)-5cos(x)=2 | | -u/u^2 | | x-7(2x-3)=2(5x-2)-3(4x+9) | | (36y^2)-5=y-18y^2 | | -2+3(x-4)=3x-9(x-3)-1 | | 7(x-8)+9=5(x-7) | | 4x-2y=800 | | 5x+3-1*2=54 | | 7(x+6)+x=4(4x+4)+6 | | 2a+7=25+8 | | .417/.875 | | 3x-2(3x-2)=6-(3x-8)+9x | | 7(x-3)+x=2(x+5)+2 | | X^2+x-2=x^3 | | 5/12/7/8 | | (-4+7i)(1+i)= | | 4(2x+5)-(8x+5)=15 | | (3x^4)/(6)=x^6/30 | | 12x/15x | | -(6-3*6)-5=-2*6-2*6+1solve |